PENGARUH HUSTLE CULTURE DAN STRES KERJA TERHADAP WORK- LIFE BALANCE PADA KARYAWAN GEN-Z DI KABUPATEN KARAWANG - Cahyani, Annisa Permata; Linda Mora; Haryanti Mustika (Universitas Bina Taruna Gorontalo, 2025)
This study aims to assess the impact of hustle culture and work pressure on the work-life balance of Gen-Z employees in Karawang Regency. The approach used in this study is quantitative, through a non-probability sampling technique with accidental sampling. The study population includes 587,125 individuals from Generation Z in the region. Based on Isaac and Michael's formula, the sample size was 349 respondents. Data analysis procedures include item analysis, reliability, classical assumption checking, hypothesis, categorization test along with the difference test. The study results indicate that hustle culture and work stress have a significant impact on work-life balance, both partially and simultaneously. Hustle culture displays a negative impact on work-life balance, meaning that the higher the level of hustle culture faced by individuals, the lower the perceived work-life balance. Conversely, job stress shows a positive correlation to work-life balance, meaning that an increase in job stress can go hand in hand with an increase in work-life balance.